2019
DOI: 10.1039/c9dt01161g
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence mechanochromism of copper iodide clusters: a rational investigation

Abstract: A photoluminescent copper iodide cluster has been characterized, and its luminescence mechanochromic properties have been anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 85 publications
1
43
0
Order By: Relevance
“…To explain the remarkable dual luminescence of 3 , we propose the following simplified energy diagram (Figure 6). As the UV spectra of 1 – 3 are due to transitions to the 1 (M+X)LCT states, the 3 CC state must be populated from the 3 (M+X)LCT one through the thermally activated channel [33–38] . The energy barrier of this process (Eadir ), estimated from the Arrhenius plot for the I HE / I LE ratio is about 220 cm −1 (Supporting Information, Figure S29 and Section 8.1).…”
Section: Resultsmentioning
confidence: 99%
“…To explain the remarkable dual luminescence of 3 , we propose the following simplified energy diagram (Figure 6). As the UV spectra of 1 – 3 are due to transitions to the 1 (M+X)LCT states, the 3 CC state must be populated from the 3 (M+X)LCT one through the thermally activated channel [33–38] . The energy barrier of this process (Eadir ), estimated from the Arrhenius plot for the I HE / I LE ratio is about 220 cm −1 (Supporting Information, Figure S29 and Section 8.1).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular cluster [Cu4I4(PPh3)4] (2) is the prototypical member in the family of cubane copper iodides coordinated by phosphine ligands and has been well characterized. 24,46,47,48 Comparing data of 1 and 2 appears thus relevant to get insights into the structure and to rationalize the photophysical properties of the coordination polymer 1.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanochromism with an impact of hydrostatic pressureonthe luminescence properties is known from related Cu 4 I 4 clusters and is mainly explained by as hortening of the CuÀCu bond lengths in the clusters accordingt ol iterature, which is however beyond the focus of this work. [10,25,43] The emission spectra in CH 2 Cl 2 strongly differ from the luminescencei nt he solid state and EtOH solution ( Figure S39). The main emission band of the complex Cu 4 I 4 (4-Me) 2 is redshifted to 680 nm, with as houlder at 540 nm.…”
Section: Luminescence Of Solutions and Neat Powdersmentioning
confidence: 99%
“…[13] At the same time, analogous tetranuclearc lusters have been reported,w hich are formally built up by combining two Cu 2 I 2 subunits. [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] At this point, it is important to mention that the very first OLED based on Cu I contained the tetranuclear complexC u 4 (CCph) 4 L 2 (L = 1,8-bis(diphenylphosphino)-3,6-dioxaoctane). [29] Lu et al reported on ah ighly luminescent tetranuclear system with aC u 4 Cl 4 core and 2-(bis(2-methyl-phenyl)phosphino)-6-methylpyridine as bridging ligand,s howinga combination of TADF and fast phosphorescence at room temperature.…”
Section: Introductionmentioning
confidence: 99%